The Corridors of Migration Control - Kelly Lytle Hernández (Migra, 2010)
On January 17, 1948, funeral home owner M. K. Fritz sat down to read his morning paper in Chicago, Illinois. In it he read about a case of racial discrimination against a Mexican national. He was so enraged by the incident that he mailed the clipping to Miguel Alemán, the president of Mexico, to let him “get a look at the way people of color are treated here in this country of ours.”¹ Fritz did not understand racial discrimination as an aberration of life in America. “We the Negro people,” he wrote “have been subject to it for a many